Design of LiAlO2 mosaic structure for preparing high nickel-based LiNi0.88Co0.07Al0.05O2 cathode material by simple hydrolysis method. (10th April 2021) - LUO, J.; Liu, J.X.; Xiao, F.M.; Huang, L.; Li, W.C.; Tang, R.H.; Zhou, Q.; Wang, Y.
Highlights: The γ-LiAlO2 -coated and Al-doped LiNi0.88 Co0.07 Al0.05 O2 have been successfully synthesized. The coating process is carried on the precursor making the coating layer uniform and continuous. Cycling performance and rate capability of LiNi0.88 Co0.07 Al0.05 O2 has been improved by coating γ-LiAlO2 and doping Al 3+ . Abstract: In order to restrain the capacity decay of nickel-rich materials for lithium-ion batteries (LIBs) in advanced energy applications, a Ni-rich cathode (LiNi0.88 Co0.07 Al0.05 O2, LANCA) with high-rate capability and cycle life was designed and prepared by coating γ-LiAlO2 and doping Al 3+ on the surface and inside of the secondary particles, respectively. Specifically, the γ-LiAlO2 -coated and Al 3+ -doped LANCA samples were synthesized by a simple strategy of pre-coating Ni0.88 Co0.07 Al0.05 (OH)2, based on aluminum isopropoxide hydrolysis combined with a post-sintering lithiation process. With the γ-LiAlO2 and Al 3+, the capacity retention ratio of the cathode is tremendously improved from 61.7 to 83.6% at 1 C rate after 100 cycles. Even at a heavy current density of 10 C for the LANCA cathode, a high reversible capacity of 154.4 mA h g − 1 can be acquired, which amount to the 82.5% capacity retention at 0.2 C. Detailed morphology and structure observation shows that the side reaction at the electrolyte-cathode interface was suppressed, the structural degradation and intergranular cracking were suppressed, while the diffusion of Li + and conductivity were improved. Therefore, this ingenious structural design has certain reference significance for the development and commercialization of high-performance cathode materials for electric power.